Recent Approaches for Manipulating Globin Gene Expression in Treating Hemoglobinopathies - Mussolino, Claudio; Strouboulis, John (Frontiers in Genome Editing, 2021)
Tissue oxygenation throughout life is secured by the activity of hemoglobin. This is composed of four monomers encoded by eight different genes whose expression is tightly regulated during development resulting in the formation of distinct hemoglobin tetramers in each different developmental stage. Mutations that alter hemoglobin structure or its regulated expression result in a large group of diseases typically referred to as hemoglobinopathies and are amongst the most common genetic defects worldwide. Unprecedented efforts in the last decades have partially unraveled the complex mechanisms that control globin genes expression throughout development. In addition, genome wide association studies have revealed protective genetic traits capable of ameliorating the clinical manifestations of severe hemoglobinopathies. This knowledge has fueled the exploitation of innovative therapeutic approaches aimed at modifying the genome or the epigenome of the affected cells to either restore hemoglobin function or to mimic the effect of protective traits. Here we describe the key steps that control the switch in gene expression that concerns the different globin genes during development and highlight the latest efforts in altering globin regulation for therapeutic puposes.